Microbiome-Aware Ecotoxicology of Organisms: Relevance, Pitfalls, and Challenges - Duperron, Sébastien; Halary, Sébastien; Gallet, Alison; Marie, Benjamin (Frontiers in Public Health, 2020)
Over the last 15 years, the advent of high-throughput ‘omics’ techniques has revealed the multiple roles and interactions occurring among hosts, their microbial partners and their environment. This microbiome revolution has radically changed our views of biology, evolution and individuality. Sitting at the interface between a host and its environment, the microbiome is a relevant yet understudied compartment for ecotoxicology research. Various recent works confirm that the microbiome reacts to and interacts with contaminants, with consequences for hosts and ecosystems. In this paper, we thus advocate for the development of a “microbiome-aware ecotoxicology” of organisms. We emphasize its relevance and discuss important conceptual and technical pitfalls associated with study design and interpretation. We identify topics such as functionality, quantification, temporality, resilience, interactions and prediction as major challenges and promising venues for microbiome research applied to ecotoxicology.